Design and fabrication of power generating treadmill - Al-Talib, Ammar Abdulaziz Majeed; They, Kai Yang; Noor Idayu, M.Tahir; Sarah ‘Atifah, Saruchi (A Life Robotics Corporation Ltd, 2023)
This paper aims to take advantage of treadmill’s wasted electrical energy during a person’s workout and utilize the energy for charging electrical appliances. The energy expended on a treadmill during the exercise is all wasted. In order to take advantage of the wasted energy, it could be harnessed by a power generator and stored in a battery bank. The electrical energy generated during the exercise on the treadmill could be utilized to power electronic devices and appliances. The attached power generation machine will not interrupt a person’s workout flow and it can be attached to any treadmill due to its friendly design. Wasted energy is harnessed in this research by a non-traditional manner of using shaft and wheel method. A multi-meter is used to measure the voltage and current and power is then calculated from the readings recorded. Tests have shown that the prototype machine is able to fully charge a 3096 mAh smartphone in 135 minutes and the phone could be fully charged for 2 charging cycles. This power generating machine is showing a good implementation for the Sustainable development Goals (SDG’s).